2019
DOI: 10.1002/bit.27237
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mAb aggregation during low pH viral inactivation and subsequent neutralization

Abstract: Monoclonal antibodies (mAbs) and related recombinant proteins continue to gain importance in the treatment of a great variety of diseases. Despite significant advances, their manufacturing can still present challenges owing to their molecular complexity and stringent regulations with respect to product purity, stability, safety, and so forth. In this context, protein aggregates are of particular concern due to their immunogenic potential. During manufacturing, mAbs routinely undergo acidic treatment to inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…The hydrophobic probe ANS is commonly used in protein folding studies as a tool for the detection of the formation of partially folded intermediates with solvent-exposed hydrophobic clusters (see, e.g. [32][33][34][35]). This dye has low fluorescence quantum yield in polar environments, such as aqueous solutions, but its fluorescence is dramatically increased in nonpolar environments.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic probe ANS is commonly used in protein folding studies as a tool for the detection of the formation of partially folded intermediates with solvent-exposed hydrophobic clusters (see, e.g. [32][33][34][35]). This dye has low fluorescence quantum yield in polar environments, such as aqueous solutions, but its fluorescence is dramatically increased in nonpolar environments.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we achieved high expression yields for our ACE2 receptor decoy, using a non-optimised transient transfection system and single-step protein-A affinity purification. The stability of the construct at pH 3.5, while showing no change in its aggregation profile and binding capacity, lends to its suitability for antibody-like purification processes such as low pH viral inactivation 45 . We have also determined an optimal pH to enhance stability of the protein using a commonly adopted His buffer for clinical-stage monoclonal antibodies 46 , raising the Tm to 52°C.…”
mentioning
confidence: 99%
“…But, at pH 4, NMR analysis established that mAb1 was in a native state with greater polypeptide conformational freedom that we attributed to intramolecular repulsions. 6,31,45,46,52 We gained deeper insight into the dynamics of mAb1 that lead to aggregation at high concentrations by adding NMR to the characterization regimen. We also showed the utility of NMR in providing insight into the pH and concentration dependent microstructures of mAb1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an earlier study of IgG1 stability in acidic conditions also reported lower aggregation rates attributed to charge-mediated repulsions, despite detecting greater exposed hydrophobic area due to greater conformational flexibility. 31 Hydrophobic interactions are also one of the major factors contributing to attractive PPI. 15,17,39,47 Although the hydrophobic surface of mAb1 is relatively unchanged over the pH range as shown by the homology modeling (Figure 2 and 1S), the impact of hydrophobic interactions may also vary with pH.…”
Section: Ph -Dependent Conformationmentioning
confidence: 99%
See 1 more Smart Citation